Association between sociodemographic factors and cholesterol-lowering medication use in U.S. adults post-myocardial infarction - Elizabeth T. Mansi; Samantha Banks; Alyson J. Littman; Noel S. Weiss (PLoS ONE, 2023)
Introduction Cholesterol-lowering medications offer effective secondary prevention after myocardial infarction (MI). Our objective was to evaluate the association between sociodemographic factors and cholesterol-lowering medication use in high-risk adults. Methods We conducted an analysis using weighted data from 31,408 participants in the 2017 and 2019 Behavioral Risk Factor Surveillance Systems cross-sectional surveys, who had a self-reported history of MI and high blood cholesterol. The sociodemographic factors evaluated were sex, age, race and ethnicity, annual household income, education level, relationship status, and reported healthcare coverage. We estimated the weighted prevalence of medication use, and weighted prevalence differences (with 95% confidence intervals) across categories, adjusting for sex, age group, healthcare coverage, smoking status, hypertension, and diabetes. Results and discussion Overall, 83% of survey participants with a self-reported history of both MI and high blood cholesterol reported currently using a cholesterol-lowering medication. The prevalence of use was only 61% in those without self-reported healthcare coverage, compared to 85% of those with healthcare coverage (adjusted prevalence difference of -20%; 95% CI: -25% to -14%). Use of cholesterol-lowering medication was relatively low in younger adults and higher in older adults, leveling off after age 65 years. The proportion of Native Hawaiian or Pacific Islanders who were using a cholesterol-lowering medication was relatively low, but otherwise there was little variation by race and ethnicity. Household income, education level, and relationship status were weakly or not associated with medication use. Conclusions Knowledge of characteristics of persons who are relatively less likely to be adherent with cholesterol-lowering medications for secondary prevention may be useful to policymakers and healthcare providers involved in the long-term treatment of MI patients. Policy makers might consider a reduced cost prescription coverage for persons without current healthcare coverage who have sustained an MI to reduce future cardiovascular morbidity and mortality.